The combined effect of graphene oxide and elemental nano-sulfur on soil biological properties and lettuce plant biomass - Hammerschmiedt, Tereza; Holatko, Jiri; Zelinka, Radim; Kintl, Antonin; Skarpa, Petr; Bytesnikova, Zuzana; Richtera, Lukas; Mustafa, Adnan; Malicek, Ondrej; Brtnicky, Martin (Frontiers in Plant Science, 2023)
Graphene oxide (GO) nanocarbon affects soil properties both negatively and positively. Although it decreases viability of some microbes, studies on how its single amendment to soil or in combination with nanosized sulfur) benefits soil microorganisms and nutrient transformation are rare. Therefore, an eight-week pot experiment was carried out under controlled conditions (growth chamber with artificial light) in soil seeded with lettuce (Lactuca sativa), and amended with either alone GO, nanosulfur (nano-S), and their combination. The following variants were tested: I. Control, II. GO, III. Low nano-S + GO, IV. High nano-S + GO, V. Low nano-S, VI. High nano-S. Results revealed, no significant differences in soil pH, dry plant aboveground and root biomass among all five amended variants and the Control. Solely applied GO exerted the most positive effect on soil respiration, which was still significant in the High nano-S + GO. Low nano-S + GO dose affected some of soil respiration types (NAG_SIR, Tre_SIR, Ala_SIR, Arg_SIR) negatively. Single GO enhanced arylsulfatase, High nano-S + GO enhanced arylsulfatase, urease, and phosphatase. The elemental nano-S probably counteracted GO-mediated effect on organic carbon oxidation. We partially proved hypothesis that GO-enhanced nano-S oxidation increased phosphatase activity.